Connecting resilience concepts to operational behaviour: A disaster exercise case study. (19th July 2021) - Pettersson, Jenny; Jonson, Carl‐Oscar; Berggren, Peter; Hermelin, Jonas; Trnka, Jiri; Woltjer, Rogier; Prytz, Erik
Abstract: Contemporary crisis management studies often make use of the concept of resilience. However, resilience as a term has a wide variety of meanings and has been criticized as lacking operationalization and empirical validation. The current study aimed to link resilience concepts to observable behaviour within a disaster medicine management system. Resilience concepts, captured in so‐called capability cards and further operationalized into six resilience prerequisites, were used in the study. An experienced crisis management team participated in a large‐scale crisis management exercise and behaviours were captured through observations, video and audio recordings. Using a markers and strategies analytical framework, two blinded raters classified observable behaviours that exemplified resilient practice. The analysis showed a high degree of agreement (79%) between the combined operationalized capability cards and resilience prerequisites and the empirical classification of behaviours. The current study shows an empirical link from resilience concepts to observable behaviours during an exercise. Observed episodic narratives exemplify empirically connected specific strategies to specific resilience markers. These results demonstrate a method with observed narratives for analyzing resilience in crisis management teams using a markers and strategies approach. Future studies can use the results to create structured observation protocols to evaluate resilient behaviours in crisis management teams.